ANTROPOLOGI PASCA “PEMBANGUNAN”: DIMENSI ANTROPOLOGI TERAPAN - Naniek Kasniyah (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2005)
This article is about Anthropology of Post Development: A dimension of Applied Anthropology. Changes in the system include the changes in content, organization, premise and value. Exploring the processes of change is a challenge to anthropology. Applied anthropology is used in the study of cultural changes. The contribution given starts from the planning until the program is over, for example, anthropologists work together with health specialists in the frame of change in the sub-culture of the recipients. Anthropology works on the whole system using holistic approach. For example, the discussion of religion cannot be separated from mythology and folklore, magi, philosophy, family, economic life, arts, belief about death, disease and curing. Another perspective of anthropology is cultural relativism where cultural and lifestyle differences can only be understood, for example in Indonesia, in the interface between midwife with modern new health elements. The popular method for data collection in anthropology is participant observation. This method is appropriate for the understanding of KAP (knowledge, attitude and practice) or cultural behavior.